2018
DOI: 10.1177/0972262918786104
|View full text |Cite
|
Sign up to set email alerts
|

Does Legal Status Affect Performance of Microfinance Institutions?: Empirical Evidence from India

Abstract: Transformation of non-government organizations (NGOs) to shareholder-owned microfinance institutions (MFIs) is an on-going debate in the field of microfinance research. Institutionalists support the transformation, whereas welfarists argue that NGOs are better conduits in serving poor clients. Prior studies on the impact of legal status of MFIs on their performance document mixed results. This study empirically investigates the extent to which the transformation is justified by examining the impact of legal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 28 publications
(59 reference statements)
1
7
0
Order By: Relevance
“…The empirical estimates of the study are in line with Wijesiri et al (2015). Furthermore, like Daher and Le Saout (2015), and Ghose et al (2018) our study found that MFIs enjoy economies of scale, as the size of scale grows the efficiency improves. This is evident from the results that when the assets base increases the MFI tends to become more financially efficient.…”
Section: Results Of Bootstrap Truncated Regressionsupporting
confidence: 78%
See 1 more Smart Citation
“…The empirical estimates of the study are in line with Wijesiri et al (2015). Furthermore, like Daher and Le Saout (2015), and Ghose et al (2018) our study found that MFIs enjoy economies of scale, as the size of scale grows the efficiency improves. This is evident from the results that when the assets base increases the MFI tends to become more financially efficient.…”
Section: Results Of Bootstrap Truncated Regressionsupporting
confidence: 78%
“…In the bank efficiency literature, plenty of studies have established the relationship between regulation, ownership structure and efficiency of Banks (See, for instance, Barth et al, 1997;Ahmad and Hassan, 2007;Shen & Chang, 2006;Pasiouras et al, 2009;Lin & Zhang, 2009;Kumar and Gulati;Boateng et al, 2015;Psillaki & Mamatzakis, 2017;). However, MFIs literature reports mixed results about the link between regulation, ownership structure and performance of MFIs (Ghose et al, 2018;Hartarska & Nadolnyak, 2007;Pati, 2012;Servin et al, 2012). Moreover, no study exists which established the association between ownership structure and efficiency of Indian MFIs in the light of regulatory reform initiated by the RBI in the Indian MFI industry after the year 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Although most microfinance services are initially operated by donation-driven Non-Governmental Organizations (NGOs), the sector is now dominated by diverse types of institutionsformal banking industry, Non-Bank Financial Institutions (NBFIs), etc. (Ghose et al, 2018). Earlier literature suggested that provision of incentives to staff, workplace norms and cultures, and some behavioral standards are dependent on the organization's governance mechanism and objectives (Merchant, 1981;Speckbacher, 2013).…”
Section: Brain Drain In Microfinance Institutionsmentioning
confidence: 99%
“…As an instance, NGOs are often regulated by a separate law (e.g. : Bangladesh), which is less stringent compared to the ones applicable to banking and financial institutions providing microfinance services (Ghose et al, 2018). Hence, the organizational objectives and governance, employee incentives and treatment, regulations, and the mechanisms of microfinance services delivery differ between the legal statuses of MFIs.…”
Section: Brain Drain In Microfinance Institutionsmentioning
confidence: 99%
“…Considering social and financial performance along with governance, Bardhan et al (2021) found interrelationship among these three factors in determining overall performance of MFIs. Ghose et al (2018) compared financial and social performance of MFIs based on their legal status and found that NGO-MFIs performs financially better as compared to NBFCs but there is no distinction among these two types of MFIs in terms of social performance. Ferro-Luzzi and Weber (2006) have conducted performance analysis of 45 microfinance institutions using factor analysis.…”
Section: Literature Reviewmentioning
confidence: 99%